THE ATTITUDES TOWARD SPORT ADVERTISING AMONG THE QUESTION HOW OFTEN CONSUMERS PURCHASE SPORTING GOODS - Stevo Popović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
This research was aimed at gaining relevant knowledge about the attitudes toward sport advertising among the question how often consumers participate in sports activities The sample included 433 respondents, divided into six subsample groups: consumers who do not purchase sport goods at all, then consumers who purchase sport goods less than ones a month, next 1-3 a month, 4-6 a month, 7-9 a month, as well as consumers who purchase sport goods more than 10 times a months. The results of the measuring were analyzed by multivariate analysis (MANOVA) and univariate analysis (ANOVA) and Post Hoc test. Based on the results it was concluded that significant differences occur at multivariate level, as well as between all three variables at a significance level of p=.05. It is interesting to highlight that it was found that the significant differences showed up between the consumers who do not purchase sport goods at all with negative attitudes and consumers who purchase sport goods less than ones a months and more with positive attitudes toward sport advertising